Synthesis and Self-assembly of a Novel Amphiphilic Tri-arm Star-shaped Copolymer Poly(ethylene oxide)-b-Poly(ε-caprolactone) - Zhang, Xiaoyan; Kang, Kexin; Wu, Tao (Letters in Organic Chemistry, 2023)
Amphiphilic tri-arm star-shaped copolymers, poly(ethylene oxide)-b-poly(ε-caprolactone) PEO3-b-PCL3, with different poly (ε-caprolactone) (PCL) molecular weights were successfully synthesized by ring-opening polymerization (ROP). Firstly, the tri-arm star-shaped PEO3 was prepared by ROP of trimethylolpropane and ethylene oxide (EO). The ring-opening polymerization (ROP) of ε- caprolactone (CL) was initiated using the tri-arm star-shaped PEO3 with the hydroxyl group as macroinitiator and Sn(Oct)2 as a catalyst. Amphiphilic tri-arm star-shaped copolymers PEO3-b-PCL3 were obtained. By changing the ratio of monomer and macroinitiator, a series of PEO3-b-PCL3 were prepared with a well-defined structure, molecular weight control, and narrow molecular weight distribution. The expected intermediates and final products were confirmed by 1H NMR and Gel Permeation Chromatography (GPC) analyses. In addition, the sizes and morphologies of the obtained micelles with different PCL segment lengths were investigated with dynamic light scattering (DLS) and transmission electron microscopy (TEM), respectively. It was found that the self-assembly morphologies were spherical micelle in aqueous solution.
Keywords: self-assembly